Management of accidental swallowing in implant dentistry - Souza, Francisley Ávila [UNESP]; Statkievicz, Cristian [UNESP]; Rosa, Ana Laura Guilhem [UNESP]; Bossi, Fabrício da Silveira (Elsevier B. V., 2015)
This report describes a protocol for managing the accidental swallowing of dental instruments in implant dentistry, illustrated by a patient who accidentally swallowed a hexagonal wrench. The first step was to refer the patient to the medical emergency hospital service for radiographic and clinical evaluation. The hexagonal wrench was located in the stomach and was immediately removed with an endoscopic procedure. The gastric mucosa was sampled via biopsy and the sample submitted to the urease test, which was positive for Helicobacter pylori. Triple treatment was instituted for gastritis caused by H pylori to avoid exposing the patient to unnecessary risk. Removal of a foreign body by means of an endoscopic procedure constitutes a safe and effective treatment.